Laboratory Study on Rockburst Control by Step Method in Deep Tunnel - Chao Ren; Xiaoming Sun; Dongqiao Liu; Jinkun Yang (Applied Sciences)
In terms of rockburst control technology, it is generally believed that optimizing the section design and adopting the step method can effectively suppress the occurrence of rockburst, but there is no literature to explain the reasons for adopting this method from the experimental point of view. In addition, compared with the application of support, this method can achieve the effect of not increasing the construction process, not affecting the progress of the project and reducing the project cost. In view of this, the Gaoloushan deep-buried tunnel with rockburst was taken as the research object in this paper. Firstly, the excavation scheme based on the step method was proposed, and its explosion-proof effect was verified again. The experimental results showed that the step method could be essentially regarded as the transformation of surrounding rock by reasonably distributing explosives and reducing the working section. The beneficial effects of this method were as follows: the release intensity of absolute energy was slowed down, the way of energy release was changed; the stress condition of surrounding rock was improved; the path of the continuous supplement of strain energy in the original rockburst area was cut off; and the energy accumulation degree of surrounding rock was reduced, so that the accumulated energy in the rock mass did not exceed its energy storage limit at the location where the rockburst should have occurred. The reduced high energy was released in an orderly manner and induced the rock failure process, forming a fracture zone and a plastic zone. In the process of expansion, the fracture zone and plastic zone further reduced the stress concentration of the surrounding rock and deteriorated the mechanical properties of the surrounding rock. The stress concentration zone was transferred to the deeper surrounding rock outside the unloading relaxation zone, and part of the elastic energy accumulated in the surrounding rock was released. The strain energy could be distributed and dissipated, and the effect of energy safety and slow release was achieved.